La visitadora social industrial en Chile : tradición y modernidad en la gestión del bienestar, 1920-1950 - Cristina Moyano B (Nuevo mundo - Mundos Nuevos, 2016)
This article discusses the establishment of the Industrial Social Service, as a professional practice of social intervention in the workplace. Through the pages of the "Journal of Social Service ", we will analyze the representations about the worker, the employer and the industrial world made by the social worker, to understand the changes in the extensive control, the bureaucratic paternalism and the many tensions between modernity and tradition lived by the social worker in the chilean industries.